Bacteroides fragilis INDUCES CONFORMATIONAL ALTERATIONS IN Trichomonas vaginalis ULTRASTRUCTURE IN AN IN VITRO INTERACTION - Souto Rodrigues, Pedro; Paola de Lima, Loyze; de Mesquita Lorete-Terra, Aline; Henrique Seabra, Sergio; Manya Bittencourt Dias Vieira, Jessica (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
Bacteroides genus are commonly found on mucous membranes, including the female genital tract, acting as agents for several site infections. Anaerobic infections are usually polymicrobial and endogenous. Trichomonas vaginalis, the trichomoniasis etiologic agent, is a facultative anaerobic flagellated parasite spread worldwide. The purpose of this study was to explore the association between vaginal bacteria and T. vaginalis, as well as to understand factors that may favour the infection of T. vaginalis. We have, therefore, used T. vaginalis trophozoites and the species Bacteroides fragilis, which is considered the most important in its genus, once it is the most commonly isolated bacteria from endogenous infections. The parasite-bacteria interaction was performed in different proportions in periods varying from 1 to 12 hours applying viability tests. The data were analyzed to compare the parasite viability in vitro in the presence and absence of B. fragilis. The results indicate that in the 1:100 proportion postinteraction analysis, ultrastructural alterations were noticeable after 6 hours. After 8 hours, T. vaginalis viability decreased, and after 12 hours of interaction no viable trophozoites were found. These data suggest that the parasite can deal with B. fragilis in short interaction periods. However, in longer interaction periods the trophozoites collapse, indicating that B. fragilis may produce toxic metabolites against T. vaginalis activity. KEY WORDS: Bacteroides fragilis; Trichomonas vaginalis; parasite-bacteria interaction; parasite environment; electron microscopy; gynecologic infections.